Generosity, greed and gambling: what difference does asymmetric information in bargaining make? - Charlotte Klempt; Kerstin Pull (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
We analyze the effects of asymmetric information concerning the size of a pie on proposer behavior in three different bargaining situations: the ultimatum game, the Yes-No-game and the dictator game. Our data show that (a) irrespective of the information condition, proposer generosity increases with responder veto power, (b) informed proposers in the ultimatum game try to exploit their superior information and hide their greed by a seemingly fair offer, and (c) uninformed proposers in the dictator game exhibit gambling behavior by asking for more than potentially is at stake. While the results of our experimental analysis are interesting as such, they may also yield interesting practical implications.
Keywords: C72; C91; 330; Bargaining; Information; Experimental Games; Verhandlungstheorie; Asymmetrische Information; Test